Efficient stereoselective synthesis of (2S,4S,5R)-(-)- and (2R,4R,5S)-(+)-bulgecinine - Chavan, Subhash P.; Praveen, C.; Sharma, P.; Kalkote, Uttam R. (Tetrahedron Letters, 2005)
A short synthetic route to (-)-and (+)-bulgecinine, the amino acid moiety of the bulgecins was achieved from the readily available nonchiral pool starting material cis-2-butene-1,4-diol in which a Claisen orthoester rearrangement and a Sharpless asymmetric dihydroxylation were used as the key steps. (C) 2004 Elsevier Ltd. All rights reserved.

Andrographolide inhibits osteopontin expression and breast tumor growth through down regulation of PI3 Kinase/Akt signaling pathway - Kumar, S.; Patil, H. S.; Sharma, P.; Kumar, D.; Dasari, Sreekanth; Puranik, Vedavati G.; Thulasiram, H. V.; Kundu, G. C. (Current Molecular Medicine, 2012)
Breast cancer is one of the most common cancers among women in India and around the world. Despite recent advancement in the treatment of breast cancer, the results of chemotherapy to date remain unsatisfactory, prompting a need to identify natural agents that could target cancer efficiently with least side effects. Andrographolide (Andro) is one such molecule which has been shown to possess inhibitory effect on cancer cell growth. In this study, Andro, a natural diterpenoid lactone isolated from Andrographis paniculata has been shown to inhibit breast cancer cell proliferation, migration and arrest cell cycle at G2/M phase and induces apoptosis through caspase independent pathway. Our experimental evidences suggest that Andro attenuates endothelial cell motility and tumor-endothelial cell interaction. Moreover, Andro suppresses breast tumor growth in orthotopic NOD/SCID mice model. The anti-tumor activity of Andro in both in vitro and in vivo model was correlated with down regulation of PI3 kinase/Akt activation and inhibition of pro-angiogenic molecules such as OPN and VEGF expressions. Collectively, these results demonstrate that Andro may act as an effective anti-tumor and anti-angiogenic agent for the treatment of breast cancer.
Keywords: Andrographolide; angiogenesis and breast tumor; migration; osteopontin; PI 3 kinase

Salvia miltiorrhiza: A medicinal herb from metabolites to pathway engineering - Gupta, S. K.; Sharma, P.; Agrawal, D. C.; Tsay, H.-S. (Medicinal plants - recent advances in research and development, 2016)
The dried, red-colored roots of Salvia miltiorrhiza (Lamiaceae) also called “danshen” in colloquial language in China have been used in traditional Chinese medicine for thousands of years to treat hypertension and other cardiovascular ailments. The main constituents of danshen are hydrophilic phenolic acids and lipophilic tanshinones. The various uses of danshen in traditional as well as modern medicines have motivated an intensive research on compounds in S. miltiorrhiza. In recent years, more than 110 compounds have been isolated from S. miltiorrhiza and their structure was identified. Tanshinones and their derivatives have been demonstrated to possess properties of slowing down or curing various ailments related to cardiovascular, cerebrovascular, respiratory, liver, nervous system, cancer, Alzheimer’s, and Parkinson’s diseases. With the increasing demand of this herb, an unrestricted collection to supply raw materials and the extraction of its constituents have severely threatened the natural habitats of S miltiorrhiza. This has prompted the researchers to develop alternative strategies for metabolite production. Several in vitro methodologies have been established to generate callus, cell suspension culture, hairy roots, and plant regeneration. Different regulators and elicitors for plant growth have been employed to enhance levels of different constituents. The advent of sequencing technologies, whole genome, and expression data has helped to provide insights and identification of pathway genes involved in the biosynthesis. This book chapter gives a brief description of in vitro methodologies, use of different elicitors, gene functions, genetic modifications, expression profiling for a better understanding, and enhancement of the constituents in S. miltiorrhiza.

Dihydropyrimidinone-isatin hybrids as novel non-nucleoside HIV-1 reverse transcriptase inhibitors - Devale, T. L.; Parikh, J.; Miniyar, P.; Sharma, P.; Shrivastava, B.; Murumkar, P. (Bioorganic Chemistry, 2017)
A novel series of substituted N-(2-( 2,3-dioxoindolin-1-yl) acetyl)-2-oxo-1,2,3,4-tetrahydropyrimidine-5carboxamide was designed, synthesized and evaluated for in vitro Reverse Transcriptase (RT) inhibitory activity. This series is a combination of peculiar structural features from leading scaffolds of [(2-hydroxye thoxy) methyl]-6-(phenylthio) thymine (HEPT) and oxyindole. In vitro screening led to identification of two hybrids (9c and 9d) possessing higher RT inhibitory activity than the standard rilpivirine. Docking study was performed to study the binding orientations of synthesized hybrids towards RT enzyme.